Catalytic Radical Intramolecular Aminoperfluoroalkylation and Aminodifluoromethylation of Unactivated Alkenes with Fluoroalkylsulfonyl Chlorides - Li, Xue-Fei; Lin, Jin-Shun; Liu, Xin-Yuan (Synthesis, 2017)
The Cu(I)/phosphoric acid (PA) dual-catalyzed radical aminoperfluoroalkylation and aminodifluoromethylation of alkenes with commercially available fluoroalkylsulfonyl chlorides as the radical source is described. Functionalized α-tertiary pyrrolidines bearing four types of fluoroalkyl groups are obtained with moderate to excellent yields. The introduction of a Cu(I)/phosphoric acid dual catalytic system and the use of silver carbonate as a key additive to inhibit the side hydroamination reaction caused by the in situ generated HCl are crucial for the transformation.
Keywords: fluoroalkylsulfonyl chlorides; aminodifluoromethylation; aminoperfluoroalkylation; radical; dual catalytic; pyrrolidines; unactivated alkenes